Integrative taxonomy approach for analysing evolutionary history of the tribe Euseiini Chant & McMurtry (Acari: Phytoseiidae). Issue 3 (3rd April 2018) - Santos, Victor Vicente Dos; Tixier, Marie-Stephane
Abstract : Phylogenetic relationships within the mite Family Phytoseiidae are little known. The presently accepted classification is based on the opinion of specialists, but not on cladistics analysis. The present paper focuses on the tribe Euseiini, containing 271 species, three subtribes and 10 genera. It aims to determine phylogenetic relationships between these taxa and test their monophyly. Molecular analysis combining six markers has been carried out for taxa we succeeded in collecting. Morphological, biogeographic and ecological data have been analysed to determine how these factors can explain the evolutionary relationships emphasized on the phylogenetic tree. Those analyses have been carried out for the taxa available for the molecular study, but also for all species of the tribe. The tribe Euseiini and the two subtribes considered are monophyletic (at least considering the available taxa), supporting the present hypothesis on Phytoseiidae classification. However, the genus Iphiseius seems to not be valid and its unique species is included in the genus Euseius . Clades that were observed within the genus Euseius do not match with recent work on species groups within this genus. It seems that some morphological features such as an insemination apparatus shape and seta length on the dorsal shield constitute some elements explaining the clusters within the genus Euseius . Biogeographic and ecological data analysis led us to hypothesize a west Gondwanian origin of the tribe Euseiini (Africa and Neotropical areas) on Rosids plants (especially of the Orders Malpiphiales and Fabales: subclass Fabidae). Further analyses are still required to (i) take into account more taxa (especially rare ones and species from the Ethiopian part), (ii) to consider more accurate morphological features through more powerful microscopic apparatus, and (iii) to associate a phylogenetic and evolutionary scenario to life traits (pollen feeders).